2018
DOI: 10.24042/tadris.v3i1.2162
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Islamic Religious Education in the Universities: The Effects on the Students' Characters in the Era of Industry 4.0

Abstract: The fourth industrial revolution (Industry 4.0) has become a major topic worldwide. The era of Industry 4.0 stimulates the advancement of science and technology through the Internet of Things (IoT), the Internet of Services (IoS), the Internet of Data (IoD) and Cyber-Physical Systems (CPS) which resulting in the creation of smart machines or autonomous robots. The era of Industry 4.0 gets rapid response worldwide, Indonesia is no exception. The Indonesian government appeals to the nation of Indonesia technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
5

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 5 publications
1
37
0
5
Order By: Relevance
“…Furthermore, the contextual variables being investigated are indeed crucial for this association, although not all aspects are essential at the same level and effect. Anwar et al (2018) suggested that character building is not only done in formal education (educational institutions), but non-formal education (parents, friends, and organizations) also has a significant impact on students. In the face of the industrial era 4.0, character building of parents, educational institutions and government are needed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, the contextual variables being investigated are indeed crucial for this association, although not all aspects are essential at the same level and effect. Anwar et al (2018) suggested that character building is not only done in formal education (educational institutions), but non-formal education (parents, friends, and organizations) also has a significant impact on students. In the face of the industrial era 4.0, character building of parents, educational institutions and government are needed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Education has a very important role in the management and preservation of the environment and natural resources (Schools, 2012). The position of education is directed at the efforts to change the behavior of students in thinking and acting (Anwar, Saregar, Hasanah, & Widayanti, 2018;O'Brien, 2010;Saputra, Jumadi, Paramitha, & Sarah, 2019;Saregar et al, 2018;Saregar, Marlina, & Kholid, 2017). If students are endeavored to think and act wisely on the environment, the environmental goals oriented towards the environment will be achieved.…”
Section: Problems Of Studymentioning
confidence: 99%
“…Educators and parents must take advantage of this opportunity to teach children to think positively, filter out good information and train the child's mindset. Strengthening character education in children and adolescents is urgent to do (Anwar, C., Saregar, A., Hasanah, U., &Widayanti, W., 2018).…”
Section: Introductionmentioning
confidence: 99%